P-selectin is a nanotherapeutic delivery target in the tumor microenvironment - Shamay, Yosi (Sci Transl Med, 2016)
Disseminated tumors are poorly accessible to nanoscale drug delivery systems because of the vascular barrier, which attenuates extravasation at the tumor site. We investigated P-selectin, a molecule expressed on activated vasculature that facilitates metastasis by arresting tumor cells at the endothelium, for its potential to target metastases by arresting nanomedicines at the tumor endothelium. We found that P-selectin is expressed on cancer cells in many human tumors. To develop a targeted drug delivery platform, we used a fucosylated polysaccharide with nanomolar affinity to P-selectin. The nanoparticles targeted the tumor microenvironment to localize chemotherapeutics and a targeted MEK (mitogen-activated protein kinase kinase) inhibitor at tumor sites in both primary and metastatic models, resulting in superior antitumor efficacy. In tumors devoid of P-selectin, we found that ionizing radiation guided the nanoparticles to the disease site by inducing P-selectin expression. Radiation concomitantly produced an abscopal-like phenomenon wherein P-selectin appeared in unirradiated tumor vasculature, suggesting a potential strategy to target disparate drug classes to almost any tumor.